Termination of probationary employment and due process: a review of Bennett Subash Peter v. Bon Ton Sdn Bhd (Bon Ton Resort Langkawi) - Ali Mohamed, Ashgar Ali (2019)
The requirement of due process before the termination of a probationer is discussed in this article with special reference to the recent Court of Appeal’s decision in Bennett Subash Peter v. Bon Ton Sdn Bhd (Bon Ton Resort Langkawi),3 where it was held, inter alia, that our industrial jurisprudence does not permit ‘termination simpliciter or arbitrary reasons for termination of a probationary employee. The reasons for non-confirmation in service must be valid and carried out bona fide.